The river as a protagonist in the formation of urban centers - the link between the São Gonçalo Beira Rio community and the Cuiabá River - Carignani, Gisele; Maciel, Sergio Dias (Technical and Scientific Journal Green Cities, 2024)
The work addresses issues related to urban rivers, with the aim of analyzing the connection between rivers and cities and the role they have played and play in Society today. Its specific object of analysis is a riverside community on the Cuiabá River, the São Gonçalo Beira Rio community. This riverside community was chosen in order to relate its historical characteristics, transformations, culture and occupation. In this way, diagnoses were presented, as well as the link that the community has established with the river since its formation and its current relations. It is a qualitative study with a bibliographical review that contextualizes the relationship established between rivers and cities since the beginning of occupations, with an emphasis on Brazil. A more in-depth study was carried out with the community, using a questionnaire to gather more precise information about the current situation of the residents and the relationships that have been preserved with the site. Through dialogues during experiences of the site and the application of questionnaires, it was possible to observe how the space is configured, as well as the possibilities of interventions and their consequences. Currently, the community’s main characteristic, its cultural expressions, is weakened. In this way, initiatives were identified that could minimize the external impacts, rescue its values and keep the community active through its culture.